The correlation between family smoking habits and mosquito coils use with pneumonia incidences in toddlers - Wiwin Winarsih; Wiwik Kusumawati; Anjarwati Anjarwati (Journal of Health Technology Assessment in Midwifery, 2019)
The incidences of pneumonia in infants Become the second highest cause mortality before reaching the age of 5 years and a health problem in Indonesia. The family of smoking and smoke from burning mosquito coils are the triggers for air pollution, which can lead to pneumonia in infants. The study aims to analyze the relationship between family smoking habits and the use of mosquito coils with the incidence of pneumonia in under-fives. The method of research applied analytic observational research using a case-control study approach. The number of samples in this study was 87 under-fives in the case group and 87 under-fives in the control group. Sampling was conducted by non-probability sampling. A questionnaire was used as a data collecting instrument. Data analysis used chi-square and multiple logistic regression. The results of this study Showed that there was a relationship between family smoking habits and the use of mosquito coils with the incidence of pneumonia in infants. In addition, there were other variables that had a relationship with the incidence of pneumonia in under-fives namely smoking location (OR = 3,046; 95% CI: 1429-6492, p = 0.003), the number of cigarettes (OR = 7.105 ; 95% CI: 3079-16394, p = 0.000), and length of time with smokers (p = 0.000). On the other hand, the variables of father smoker status and the frequency of using mosquito coils were not related to the incidence of pneumonia in under-fives (p value 0.05). It is concluded that family smoking habits, use of mosquito coils, the location of smoking, and number of cigarettes, and  length of time together with smokers were risk factors associated with the incidence of pneumonia in toddlers